THE MORAL CRISIS OF INFLUENCERS AND VIRAL CONTENT THAT IS NOT EDUCATIONAL - Nurlatifa, Nurlatifa; Basariah, Basariah (SYNTIFIC, 2025)
Background. In Indonesia, the rapid growth of internet access and social media, with around 77% of the population online by 2022, has coincided with a decline in human values. A 2021 report documented over 1,000 instances of negative content on social media, revealing issues of discrimination and violence amidst technological progress. This evolution in communication has fostered influencer marketing, significantly shaping public opinion and behavior. Research Purpose. To analyze the moral crisis of influencers and viral contents that is not education-based on Pancasila, the second principle. Research Method. This study utilizes a qualitative-systematic literature review to evaluate the influence of social media influencers on public opinion in Indonesia. It involves a systematic search of databases like Google Scholar and Science Direct for literature from 2019 to 2024, ensuring relevance in the rapidly changing social media landscape. The research incorporates keywords such as